Effects of Uniform or Multi-Gradient Equilibration During Vitrification on Mitochondrial Damage in Mouse Oocytes - Eun Hee Yu; Jung Ran Cho; Ha Eun Jung; Hyun Joo Lee; Jong Kil Joo (Clinical and Experimental Obstetrics & Gynecology)
Background: Oocyte cryopreservation is a crucial technique in contemporary society since it provides a means for future fertility preservation at a time when delayed marriage and pregnancy are common. However, oocyte cryopreservation remains challenging because of the inherent vulnerability of oocytes becoming damaged during freezing and thawing. This study investigated the effects of uniform versus multi-gradient equilibration during vitrification on mitochondrial integrity and distribution in mouse oocytes. Methods: We compared a conventional uniform equilibration method involving a 10-minute exposure to cryoprotective agents using a multi-gradient equilibration method that reduced the exposure time to 2.5 minutes. The survival rates of the vitrified oocytes and the mitochondrial fluorescence intensity and distribution were assessed using confocal microscopy. Results: The survival rates were not significantly different between the two methods. However, the multi-gradient equilibration method presented a higher mitochondrial fluorescence intensity and more uniform distribution, indicating better preservation of mitochondrial function. Conclusion: These findings suggest that the multi-gradient equilibration method may offer a viable alternative to conventional vitrification that can reduce mitochondrial damage and potentially improve oocyte quality post-thawing.